106 A CASE OF COMPLETE ATRIOVENTRICULAR BLOCK AND ALTERNATING BUNDLE BRANCH BLOCK DUE TO FULMINANT MYOCARDITIS. (15th December 2022) - Maione, Davide; Lalario, Andrea; De Luca, Antonio; Altinier, Alessandro; Carriere, Cosimo; Merlo, Marco; Sinagra, Gianfranco
Abstract: A 41-year-old man, without previous cardiological history, presented at the emergency department with hypotension and multi-organ failure. Laboratory testing showed elevated white cell blood count (16780/mcL; normal value 4000-11000/mcL; 90% neutrophils), high-sensibility troponin I (23247 ng/L; normal value <18 ng/L) and NT-pro-BNP (21914 pg/mL; normal value <300 pg/mL). At electrocardiogram (EKG) there was sinus rhythm with complete atrioventricular block and alternating right and left bundle branch block. Echocardiography revealed a moderate left ventricular (LV) dilatation, mild LV hypertrophy, severe biventricular dysfunction (LV Ejection Fraction - EF - 30%) with dense spontaneous echo contrast and moderate pulmonary hypertension (systolic pulmonary artery pressure 51 mmHg). After positioning a temporary pacemaker, the patient was transferred to our Cardiac Intensive Care Unit. After initial hemodynamic stabilization with endovenous inotropes, diuretics, and mechanical circulatory support (intra-aortic balloon pump), coronary angiography was performed showing normal coronary arteries. Since fulminant myocarditis was suspected and magnetic resonance was not feasible due to the patient's instability, an endomyocardial biopsy (EMB) was performed with the evidence of myocardial edema, initial myocardial fibrosis, and the concomitant presence of lymphocytic and eosinophilic endo-myocarditis (despite normal eosinophilic blood count) without evidence of active viral replication. After careful exclusion of latent or active infections, high doses of corticosteroids and azathioprine were initiated, with rapid laboratoristic and clinical response. EKG showed AV block regression and QRS width's normalization, so the pacemaker was removed. LVEF rapidly improved and was completely normalized at discharge after two weeks. In the early follow-up, a cardiac magnetic resonance (CMR) was performed with evidence of persistency of mildly dilated LV, normalization of LV wall thickness and biventricular function, a diffuse increase of T1 relaxation time, increased T2 signal of the anterior and septal walls, and intramural anteroseptal late gadolinium enhancement (LGE). Fulminant myocarditis is a rare presentation of acute myocarditis, with low incidence but high mortality. The inflammation of the myocardium itself leads to acute heart failure, cardiogenic shock, and cardiac arrhythmias, including sinus arrest, AV block, ventricular tachycardia, and ventricular fibrillation during the acute phase. In our case, AV block could be an expression of anteroseptal involvement, documented at CMR. This localization has already been associated with worse clinical presentation and could be a marker of poor prognosis. Diagnosis and treatment of fulminant myocarditis require EMB, to obtain information about the etiology and active viral replication in the heart tissue. In our case, the florid inflammatory state and the absence of viral replication allowed prompt treatment with immunosuppressors, with a quick and full recovery of biventricular function in only two weeks.